Measuring displacements in engineering structures by means of a coordinate laser stadion = Badanie przemieszczeń obiektów inżynierskich z wykorzystaniem stacji laserowej - Sztubecki, Jacek; Bujarkiewicz, Adam; Sztubecka, Małgorzata (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The application of geodetic methods to examine structures consists in the determination of their displacements relative to an established geodetic reference datum or in the definition of the geometry of their individual components. Such examinations form a picture of changes happening between specific points in time.
Keywords: displacement measurement; laser station; engineering structures; dynamic response; bridge structures; pomiar przemieszczeń; stacja laserowa; monitorowanie obiektów inżynierskich; dynamika konstrukcji; konstrukcje mostowe